What Has the Pandemic Revealed about the Shortcomings of Modern Epidemiology? What Can We Fix or Do Better?. Issue 6 (27th January 2022) - Dimitris, Michelle C; Galea, Sandro; Marcus, Julia L; Pan, An; Sander, Beate; Platt, Robert W
Abstract: In this commentary, we discuss themes that emerged from our symposium about what modern epidemiology as a science may learn from the COVID-19 pandemic. We reflect on the successes and limitations of this discipline from multiple perspectives, including from junior and senior epidemiologists and scientists on the front lines of generating evidence for the COVID-19 pandemic response in Wuhan, China, to Ontario, Canada. These themes include the role of the traditional scientific process in a public health emergency; epidemiologic methods and data that are critical for an effective pandemic response; the interventions that epidemiologists recommended and interventions that we may explore in the future; inequitable impacts of the COVID-19 pandemic contrasted with homogeneity in the epidemiologist workforce; effective and honest communication of uncertainty; trust and collaboration; and the extent to which these themes are currently reflected in our training programs and discipline. We look forward to insights from field epidemiologists directly involved in the ongoing response to the COVID-19 pandemic and further reflection from epidemiologists throughout our discipline.